Lessons from beyond the Great Wall: what cross-cultural management researchers can learn from the Middle Kingdom. (4th March 2010) - Lo, Kevin; Michailova, Snejina
This paper revisits three studies conducted in the context of China to demonstrate how a single culture has eluded explanation by some of the most well-known cross-cultural studies as well as rendered valid, reliable scales from Western contexts inadequate in that culture. We suggest that cross-cultural researchers can utilise less-explored research contexts to further develop the sophistication of research by: a) identifying emics; b) aiming at cultural completeness; c) contextualising and meaningfully incorporating indigenous thought and knowledge. Looking beyond the three studies, we address the issue of intra-cultural variation, which can assist us to formulate truly cross-cultural approaches, both conceptually and methodologically, and to capture cross-cultural differences that might otherwise be lost to pseudo-etic or parochial approaches.